School Belonging and Reading Literacy: A Multilevel Moderated Mediation Model - Tan, Yuting; Fan, Zhengcheng; Wei, Xiaoman; Yang, Tao (Frontiers in Psychology, 2022)
School belonging is of great significance to students' physical and mental health development, especially academic improvement. However, the mechanism of the influence of school belonging on student academic achievement should be further explored, especially reading performance. Based on ecological systems theory and self-determination theory, the present research constructs a multilevel design to examine a moderated mediation model in which school belonging as a level-1 predictor, mastery goal orientation as a level-1 mediator and school disciplinary climate as a level-2 moderator jointly impact reading literacy. Results of the study were based on the questionnaires from 11,364 (5,455 girls and 5,909 boys)15-year-olds nested in 332 schools in mainland China that participated in PISA 2018. The cross-sectional analysis indicated that: (1) school belonging had a direct and positive effect on student reading literacy; (2) the relationship between school belonging and reading literacy was prominently mediated by mastery goal orientation; (3) both school disciplinary climate level and strength could negatively moderate the latter half path of "school belonging → mastery goal orientation → reading literacy". Implications, limitations, and future research directions are discussed.